1997
DOI: 10.1159/000203675
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Transmission of Hepatitis C in Household Contacts of Children with Homozygous β-Thalassaemia

Abstract: Forty-eight household contacts of 25 children with homozygous β-thalassaemia and chronic hepatitis C (index cases) were evaluated for antibodies against hepatitis C virus (HCV) and increased transaminase values in the blood. The mean age ± SD of the household contacts was 36.4 ± 17.0 years (range 5-67) and 20 of them were males. All thalassaemic patients (age 14.3 ± 3.0 years, range 8-19) were positive for anti-HCV antibodies by repeated determinations. HCV-RNA was detected in the blood of 22 of 23 patients te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The possibility of sexual and non-sexual intrafamilial transmission has been identified using molecular methods [Chayama et al, 1995;Demelia et al, 1996]. Some investigators reported an increased risk in the siblings of HCV carriers as well as their children and sexual partners [Vegnente et al, 1994;Demelia et al, 1996;Papanastasiou et al, 1997]. In this study, bivariate analysis failed to reveal any significant risk resulting from living with a person (any relation) with acute or chronic hepatitis or jaundice.…”
Section: Discussionmentioning
confidence: 56%
“…The possibility of sexual and non-sexual intrafamilial transmission has been identified using molecular methods [Chayama et al, 1995;Demelia et al, 1996]. Some investigators reported an increased risk in the siblings of HCV carriers as well as their children and sexual partners [Vegnente et al, 1994;Demelia et al, 1996;Papanastasiou et al, 1997]. In this study, bivariate analysis failed to reveal any significant risk resulting from living with a person (any relation) with acute or chronic hepatitis or jaundice.…”
Section: Discussionmentioning
confidence: 56%
“…47 A Greek study found no anti-HCV antibodies in household contacts of 23 HCV-RNA-positive thalassemia patients with chronic hepatitis during a mean observation of 4 years. 48 Conversely, a cross-sectional study performed in Pakistan found that 20.5% of 341 household contacts of 86 anti-HCV-positive children with thalassemia had anti-HCV antibodies. 49 In another study, performed in India, 16% of 125 first-degree relatives of thalassemia patients with chronic HCV infection were found to be positive for anti-HCV.…”
Section: What Proportion Of Thalassemia Patients Have Chronic Viral Imentioning
confidence: 97%
“…47 A Greek study found no anti-HCV antibodies in household contacts of 23 HCV-RNA-positive thalassemia patients with chronic hepatitis during a mean observation of 4 years. 48 Conversely, a cross-sectional study performed in Pakistan found that 20.5% of 341 household contacts of 86 anti-HCV-positive children with For personal use only. on May 12, 2018. by guest www.bloodjournal.org From thalassemia had anti-HCV antibodies.…”
mentioning
confidence: 98%
“…Almost 5% HCV infections are caused by needle stick injury [29,30]. 3% to 5% infants acquire HCV from infected mother by perinatal transmission [31]. HCV is present in saliva and milk but transfer of HCV infection through breast milk has not been reported [32,33].…”
Section: Introductionmentioning
confidence: 99%